Themes of U.S. Wine Advertising and the Use of Geography and Place to Market Wine - John P. Tiefenbacher (EchoGéo)
This paper describes and discusses the role of geography in the advertising of wine in a popular American wine magazine, The Wine Spectator. Systematic assessment of the visual and textual contents of 764 advertisements that appeared in 30 issues (2 years of the publication) reveals that approximately 66% of advertisements contained geographical components that clearly suggest that place is important in the production and quality of wine. A mixed-methods qualitative approach yielded eight identifiable messages and eleven distinct themes reflected in these advertisements. The most important of these relate the importance of place and landscape to the quality of wines. Explicit use of the notion of terroir is but one component of contemporary wine advertising and may reflect a movement toward the “down-scaling” of the wine industry, reflecting a shift from the era of mass production of wine by large corporations to a proliferation of smaller producers who are intimate with the places and conditions of production. This study establishes a baseline for further research that can compare past approaches to advertisements and relative importance of geography in wine advertising.